1979
DOI: 10.1111/j.1471-0528.1979.tb11255.x
|View full text |Cite
|
Sign up to set email alerts
|

Real‐time Ultrasound Observation of Fetal Activity in Labour

Abstract: Fetal activity was observed by realtime ultrasound for one hour in 25 patients in labour. Fetal respiratory movement, although reduced compared to the antenatal period, was observed in 13 patients. In three patients, hiccough-like movements were noted. Fetal body and/or extremity movements were observed in all patients (mean 41/hour) and frequently occurred in episodes. These bursts of movements were significantly correlated with contractions and fetal heart rate (FHR) accelerations. There was a significant as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…RICHARDSON et al [8] found no fetal respiratory movements. While BOYLAN et al [2] and WHITTMANN et al [12] reported decreased fetal breathing movements in active labor. This study was undertaken to evaluate the normal pattern of fetal activity in labor.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…RICHARDSON et al [8] found no fetal respiratory movements. While BOYLAN et al [2] and WHITTMANN et al [12] reported decreased fetal breathing movements in active labor. This study was undertaken to evaluate the normal pattern of fetal activity in labor.…”
Section: Discussionmentioning
confidence: 97%
“…BOYLAN et al [2] who studied 22 patients during labor, found that fetuses spend 36% of their time making breathing movements antenataly but this decreased to less than 1% during labor. WHITTMANN et al [12] who observed fetal activity by realtime ultra-sound for one hour in 25 patients in labor, found fetal respiratory movements in 13 patients, but reduced compared to the antenatal period. Fetal body and/or extremity movements were observed in all patients.…”
Section: Introductionmentioning
confidence: 97%
“…Fetal body movements are frequently associated with uterine contractions [6,7,10]. It is possible that the increase of the BTBV during periods of increased fetal activity as reported in some studies was actually caused by uterine contractions.…”
Section: Discussionmentioning
confidence: 99%
“…As it is known that fetal body movements frequently occur during uterine contractions [6,7], we undertook a study in order to investigate whether changes in BTBV during labor could be contributed to both these fac tors, namely uterine contractions and fetal movements, or only to one of them.…”
Section: Introductionmentioning
confidence: 99%
“…The collateral applicability of ultrasound during labor has also been studied in literature. For example, assessment before epidural catheter placement, 2-8 intrapartum maternal symphyseal separation by transverse suprapubic ultrasound examination, 9 intrapartum fetal behavior and prediction of adverse perinatal outcome based on amniotic fluid amount or biophysical profile, [10][11][12][13][14][15][16][17][18][19] depiction of the molding and caput succedaneum during, but also before labor, [20][21][22][23][24][25][26] maternal 27,28 and fetal [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] intrapartum pulsed Doppler blood flow assessment, intrapartum myometrial thickness changes, 44 ultrasound use in the third stage of labor, [45][46][47][48][49][50][51][52] or the assessment of the postvoid residual volume in laboring and postpartum women w...…”
Section: Ultrasound In Prelabormentioning
confidence: 99%